Політико-культурні чинники мобілізації до політичної участі - Ямельницький, Олег (Видавництво Львівської політехніки, 2014)
Розглянуто значення політико-культурних чинників, які визначають спрямованість та форми дій з мобілізації політичної участі громадян. Наголошено, що особливе значення під час вивчення мобілізаційних механізмів активізації політичної участі належить джерелам активності – мотивам та мотивації. Досліджено сукупність мотиваційних сфер, щодо яких можуть бути застосовані чинники мобілізації: організаційно-практичної (утилітарної) мотивації; організаційно-інституційної мотивації; організаційного менталітету. The role of political and cultural factors that determine the direction and the forms of actions that comes from the mobilization of the political participation of citizens is observed. It is noted that the particular importance in the study of the mechanisms of activation of the mobilization of political participation belongs to sources of activity – the motives and motivations that determine its important parameters such as energy, direction and duration. The work investigates a set of motivational areas for which can be applied the mobilization factors: organizational and practical (utilitarian) motivation (a group of specific factors of mobilization that are related with benefits and the practical usage), organizational and institutional motivations (factors that are related to the creation of the sustainable social and organizational experience of a joint activity, the activation of grouped, substructural and intergroup relations and communications), the organizational mentality (the system of underlying values that pre-determines the position of the personality in a complex system of a social relations). It is argued about the need for the formation of participatory civil society that is characterized by the transition from «the cultural domination» to «the culture of coordination»; the substitution principle «knowledge is a power» to «knowledge is the possibility of action», the transition from elite to mass political communication, from elitist to participatory democracy, a combination of vertical and horizontal authority in networked democracy, the representative democracy, in lieu of mass direct participation by means of a mass communication; the departization and the decentralization of the apparatus of a state power, etc.
The political and cultural factors of mobilization towards the political participation
Keywords: політична мобілізація; політична культура; мотиваційні сфери; мотив-спонукання; мотив-готовність; мотив-цінність; демократія; political mobilization; political culture; motivational spheres; motive inducement; motive willingness; motive value; democracy